Diversidad de inclusiones minerales en la subtribu Oncidiinae (Orchidaceae) - Sandoval-Zapotitla, Estela (2010)
Mineral inclusions in plants, of different chemical constitution and forms, have been studied in some plant groups and are cur-rently used as diagnostic tools in taxonomic identifications. With the aim to identify their possible application in taxonomy, mineral inclusions in the leaves of 140 species of Oncidiinae (Orchidaceae) were analyzed and compared. Leave transversal sections were studied with the aid of clear field, phase contrast, and polarized light microscopy. Crystals commonly occured in mesophyll cells, and only in two species those were observed in epidermal cells. Several forms of calcium oxalate crystals and silicdioxide deposits in the form of stegmata were found. The most common crystalline forms were raphides, prisms and druses. Nevertheless, crystals like sands, and concentric and radial plates were also observed in few species. These crystalline forms of concentric and radial plates are reported for the first time in Oncidiinae and Orchidaceae. The stegmata are conical with rough surface, forming tiers along with fibers. Stegmata commonly occur in the vascular bundle sheath and in the abaxial or adaxial fiber bundles. However, few species do not have stegmata in fiber bundles and other species lack both. The taxonomic importance of these mineral inclusions is discussed for the different clades, genera or species within the subtribe Oncidiinae.